Elaboración de compost mediante la utilización de sustancias aceleradoras (yogurt, levadura, melaza, jugo de caña de azúcar) para la descomposición de los sustratos orgánicos. - Duque Herrera, Gilmar Ariel (2019)
Organic fertilizers are a source of bacterial life for the soil and necessary for plant nutrition, enabling nutrient degradation and allowing plants to resemble it better, and thus improving crop development, current research led to carried out in order to find response variables to the problems that arise when using substances that lead to compost to accelerate its decomposition process as well as make it have better physical properties, assuming the benefits offered by compost, the The objective of this test is to evaluate the compost elaboration by means of the use of accelerating substances (yogurt, yeast, molasses, sugar cane juice) for the decomposition of organic substrates. The study was carried out at the “State Technical University of Quevedo”, Experimental Campus “La María located at Km 7.5 of the Vía Quevedo - El Empalme. A completely randomized design (DCA) was handled with five treatments in three repetitions, the treatments being: yeast, molasses, sugar cane juice, yogurt and a control. Molasses treatment decreased the decomposition period by 3 days in relation to the control. The results of the temperature estimates both at the beginning and at the end of the trial did not show significant divergences, demonstrating that the molasses treatment showed a greater temperature drop with 6.6 ° C. The moisture content of the mounds with the application of the different substances added, did not register significant differences, registering averages that ranged between 56.3 and 58.3%. Applying molasses obtained a lower final weight with 36.80 Kg, reflecting a weight loss of 8.70 Kg, can reflect a better process of decomposition of matter. The nutritional content of the compost mounds with the addition of the treatments under study did not differ significantly. The treatment with molasses represents a great option since it facilitates the obtaining of compost with better characteristics. Keywords: Compost, organic fertilizers, accelerators.